Full-time physioxic culture conditions promote MSC proliferation more than hypoxic preconditioning - Henn, A.; Darou, S.; Yerden, R. (Cytotherapy (Oxford, England), 2019)
Cells that are cultured and handled in traditional hyperoxic room air experience a dramatic shift in oxygen levels when injected in vivo. It has been reported that hypoxic pre-conditioning of mesenchymal stromal cells (MSC) in culture can increase cell survival in vivo after administration. Published hypoxic pre-treatments subject room-air expanded cells to lower oxygen atmospheric conditions for lengths of time that range from 15 minutes to 36 hours, followed by another period of high oxygen exposure in room air conditions before administration. Some regimens use cobalt compounds to deplete HIF-1a rather than the cell environment. We previously showed that Human bone marrow MSC yields are improved by enclosing cell-handling processes as well as incubation for a full-time controlled physioxic atmosphere. To use the Xvivo System (BioSpherix), with fully-enclosed and environmentally-controlled cell incubation and handling chambers, to compare different hypoxic pre-conditioning regimens to full-time physioxic conditions for MSC yields and subjected to subsequent physioxic conditions as if injected venously. Our null hypothesis was that the different culture conditions make no difference to MSC morphology and proliferation rates. MSC were incubated for 1-36 hours at 1% O2 before return to traditional supraphysioxic room air incubator oxygen levels for 24 hours. The cells were then incubated at 5% O2 (venous O2 levels) as if injected in vivo. These conditions were compared with unbroken 5% O2 for both cell handling and culture. Using an immersion oxygen probe, we recorded vessel headspace and pericellular medium oxygen levels during each regimen. For 72 hours in culture to 5% O2, we assayed cells for changes in cell division rates and final cell yield. MSC pericellular O2 levels lagged far behind atmospheric oxygen level changes, so MSC experienced low oxygen conditions for far less time than the pre-conditioning period. Unbroken oxygen conditions were more favorable for keeping MSC in the cell cycle than any pre-conditioning regiment, disproving the null hypothesis. We concluded that hypoxic pre-conditioning is not as favorable for MSC yields as full-time physioxic conditions for cell handling and incubation.